Preliminary Study Analysis of 3D Printing Process Of Artificial Vascular Models Using Additive Manufacturing - Fakhril Husain; I Gusti Bagus Budi Dharma (Politeknik STMI Jakarta, 2024)
Manufacturing technology is developing very rapidly, especially in the production process production process. One of them is the emergence of additive manufacturing technology. One type of additive manufacturing is stereolithography (SLA) which is applied in the world of health. Many factors in the success of the print process of additive manufacturing technology. One of the important factors is the process parameter, namely build orientation. In addition, post processing is also an influential factor in production success. This research analyses the best production process by looking at the effect of print position at 0°, 45° and 90°. This research is applied to This research uses experiments by printing the product. printing the product. The material used is a flexible material, Anycubic Though Resin, with the help of a 3D printer, Anycubic Photon Monon. printer Anycubic Photon Mono X. The printing process uses the same parameters in the 0°, 45° and 90° positions. The three positions produce defective results that are not significantly different, with the most optimal results obtained at the 0° position. However, support settings must be considered because they affect the success of the product as well as the amount of resin used. The study also found that the best post processing is resin cleaning without the use of rotating machine and without the use of curing. This is because it will damage the the product and change the mechanical properties.